2022
DOI: 10.4235/agmr.22.0023
|View full text |Cite
|
Sign up to set email alerts
|

A Malay Version of the Attitude to Ageing Questionnaire: Its Adaptation, Validation, and Reliability in the Malaysian Older Adult Population

Abstract: Introduction:The Attitude to Ageing Questionnaire (AAQ) was developed to assess perceptions of the aging process among older adults. The 24 items were framed into three factors. This study aimed to translate the AAQ from English to the Malay language (AAQ-M) and determine its factorial structure and validity in a Malaysian population. Methodology: The original AAQ underwent a standard translation process, as well as content and face validation, to produce the AAQ-M. The construct validity of the AAQ-M was then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…In our study, AAQp emerges as a short and valid instrument when one intends to evaluate attitudes towards aging. As found in previous studies, both with the English [9] and non-English versions [13,21], AAQp showed overall acceptable to good reliability (with Cronbach's alphas ranging 0.77 to 0.65). Furthermore, composite reliabilities were achieved but not the convergent validity, as AVE values were lower than .50.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In our study, AAQp emerges as a short and valid instrument when one intends to evaluate attitudes towards aging. As found in previous studies, both with the English [9] and non-English versions [13,21], AAQp showed overall acceptable to good reliability (with Cronbach's alphas ranging 0.77 to 0.65). Furthermore, composite reliabilities were achieved but not the convergent validity, as AVE values were lower than .50.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, using the measure of attitudes towards aging benefits development theory and may help innovate anti-ageism-based interventions [22,39]. Finally, with the measure now presented, it is possible to correlate attitudes towards aging with creative adaptability in Portuguese-speaking contexts and compare it with other cultural contexts [21,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the literature in the field of ageing stresses the need for more research, especially randomized clinical trials [ 20 ], which to this extent, justifies the effort to validate and adapt valid measuring instruments. In addition, some authors [ 21 , 22 ] have even suggested conducting studies on ageism in different cultural contexts. Therefore, the present study allows both to make the AAQ a stronger and more valid instrument and develop future studies on the ageing process and mental health variables [ 1 , 23 ].…”
Section: Introductionmentioning
confidence: 99%